Socioeconomic factors for sports specialization and injury in youth athletes - Jayanthi, N. A.; Holt, D. B.; LaBella, C. R.; Dugas, L. R. (Sports Health: A Multidisciplinary Approach, 2018)
Background: The effect of socioeconomic status (SES) on rates of sports specialization and injury among youth athletes has not been described previously. Hypothesis: Young athletes from lower socioeconomic status will have lower rates of sports specialization and subsequently lower risk of overuse injuries. Study Design: Cohort study. Level of Evidence: Level 3. Methods: Injured athletes aged 7 to 18 years were recruited from 2 hospital-based sports medicine clinics and compared with uninjured athletes presenting for sports physicals at primary care clinics between 2010 and 2013. Participants completed surveys on training patterns. Electronic medical records provided injury details as well as patient zip code, race, and health insurance type. SES was estimated from zip codes. The sample was divided into SES tertiles. Analysis of variance and multivariate regression were used for continuous variables, and multivariate logistic regression analyses were conducted to explore relationships between risk factors and injury. Results: Of 1190 athletes surveyed, 1139 (96%) had satisfactory SES data. Compared with low-SES athletes, high-SES athletes reported more hours per week spent playing organized sports (11.2 ± 6.0 vs 10.0 ± 6.5; P = 0.02), trained more months per year in their main sport (9.7 ± 3.1 vs 7.6 ± 3.7; P < 0.01), were more often highly specialized (38.9% vs 16.6%; P < 0.01), and had increased participation in individual sports (64.8% vs 40.0%; P < 0.01). The proportion of athletes with a greater than 2:1 ratio of weekly hours in organized sports to free play increased with SES. Accounting for age and weekly organized sports hours, the odds of reporting a serious overuse injury increased with SES (odds ratio, 1.5; P < 0.01). Conclusion: High-SES athletes reported more serious overuse injuries than low-SES athletes, potentially due to higher rates of sports specialization, more hours per week playing organized sports, higher ratio of weekly hours in organized sports to free play, and greater participation in individual sports. Clinical Relevance: As SES increases, young athletes report higher degrees of sports specialization, greater participation in individual sports, and more serious overuse injuries.